2016
DOI: 10.5114/ceji.2016.65139
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of selected markers and apoptotic pathways for pancreatic cancer

Abstract: Pancreatic cancer occupies the fourth place as a cause of death from cancer, and the mortality rate is similar to the number of newly detected cases. Due to the late diagnosis, only 5-6% of patients with pancreatic cancer survive for five years. Given that early diagnosis is critical for improving patients’ survival rates, there is an urgent need for the discovery and validation of new biomarkers with sufficient sensitivity and specificity to help diagnose pancreatic cancer early. Detection of serum tumor mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…Micro ribonuclease acids (miRNAs), micro, non-coding RNAs of length 20–25 nt, are members of hairpin structure precursors, which are capable of interacting with the 3' non-coding region of the target mRNAs. miRNA plays an important role in post-transcriptional regulation of eukaryotic gene expression, which is crucial to cell proliferation, differentiation, migration, apoptosis, and regulation of cell cycle (35). At present, numerous studies have demonstrated that miRNAs could be treated as diagnostic biomarkers for multiple cancers (6, 7), and researchers come to realize the importance of better understanding of the pathogenesis of BC and identification of the new prognostic biomarkers for BC (8).…”
Section: Introductionmentioning
confidence: 99%
“…Micro ribonuclease acids (miRNAs), micro, non-coding RNAs of length 20–25 nt, are members of hairpin structure precursors, which are capable of interacting with the 3' non-coding region of the target mRNAs. miRNA plays an important role in post-transcriptional regulation of eukaryotic gene expression, which is crucial to cell proliferation, differentiation, migration, apoptosis, and regulation of cell cycle (35). At present, numerous studies have demonstrated that miRNAs could be treated as diagnostic biomarkers for multiple cancers (6, 7), and researchers come to realize the importance of better understanding of the pathogenesis of BC and identification of the new prognostic biomarkers for BC (8).…”
Section: Introductionmentioning
confidence: 99%
“…According to the ACS, the morbidity of pancreatic cancer will equal around 53,670 and the mortality, about 43,090 in 2017 in the USA [ 1 ]. Thus, it is vital to study the biology of pancreatic ductal adenocarcinoma because it may contribute to better diagnostics and development of new, more efficient therapeutic methods [ 2 ]. Formulating the model of gradual progression of pancreatic cancer and proving that it develops from the precursor lesions, including the most frequent intraepithelial neoplasia of the pancreas, have become a significant step in the research into pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In PDAC patients, it is widely recognized that CA 19-9 is a clinically useful biomarker for determining resectability, a prognostic marker after resection, and a predictive marker for response to chemotherapy [33,34]. In contrast, CEA has low sensitivity and specificity for diagnosing PDAC, although it is often used in combination with other tumor markers, such as CA 19-9 [35,36,37]. In patients who underwent pancreatectomy, a combination of preoperative CA 19-9 and CEA effectively improved the prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%